Shoaling and Factors Underlying Shoal Composition in Fish - Piyapong, Chantima (KKU Science Journal, 2012)
This article reviews group-living of animals, by focusing on shoaling behaviour in fish. It provides a general overview of shoaling behaviour, costs and benefits of this behaviour, and also factors which may underlie shoal composition or influence the decision of an individual to join a shoal. These include species, sex, phenotypic assortment, parasite load, familiarity and kinship.